2015
DOI: 10.1016/j.renene.2014.12.070
|View full text |Cite
|
Sign up to set email alerts
|

Selective conversion of starch to glucose using carbon based solid acid catalyst

Abstract: a b s t r a c tActivated carbon supported silicotungstic acid is used as catalyst for the hydrolysis of starch to glucose. The selectivity of the hydrothermal process for glucose production is demonstrated. Byproducts such as levulinic and formic acids are not formed. Separation of the catalyst is easy, and the catalyst reusability is demonstrated in five consecutive reaction runs. No appreciable loss in activity and selectivity of the catalyst is observed even after 5 consecutive reaction runs. Leaching of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…From 31.5 wt% starch in the high carbohydrate algae, the expected glucose amount upon complete hydrolysis is 35 wt% (ref. 43) which corresponds to a theoretical ethanol yield value of 17.8 wt%. Under the optimized process conditions, 16 wt% ethanol could be obtained from the high carbohydrate algae which corresponds to a process efficiency of 89%.…”
Section: Effect Of Starch Content Of Ulva Rigida On Bioethanol Yieldmentioning
confidence: 91%
“…From 31.5 wt% starch in the high carbohydrate algae, the expected glucose amount upon complete hydrolysis is 35 wt% (ref. 43) which corresponds to a theoretical ethanol yield value of 17.8 wt%. Under the optimized process conditions, 16 wt% ethanol could be obtained from the high carbohydrate algae which corresponds to a process efficiency of 89%.…”
Section: Effect Of Starch Content Of Ulva Rigida On Bioethanol Yieldmentioning
confidence: 91%
“…[13][14][15][16] Glucose is a monosaccharide with extensive natural sources and can be obtained from biological refining. 17,18 In the wave of green development, glucose-type compounds can be used as a potential target of green chemical industry. It has low toxicity and is easy to biodegrade, which is very attractive for environmental protection.…”
Section: Introductionmentioning
confidence: 99%
“…Glucose is a monosaccharide with extensive natural sources and can be obtained from biological refining 17,18 . In the wave of green development, glucose‐type compounds can be used as a potential target of green chemical industry.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfonated carbon catalyst derived from lignin was proven to be efficient for the hydrolysis of starch with high total reducing sugar yield (≈96.5%, w/w) . The selective conversion of starch to glucose by means of carbon‐based solid acids has been also explored, resulting in high glucose yields (≈94%, w/w) . Sun et al reported that (C 16 TA)H 5 P 2 W 18 O 62 nano‐assembly performed 94.8% conversion of cellulose into methyl levulinate with 58.5% yield in methanol.…”
Section: Introductionmentioning
confidence: 99%